Определение тепловых потерь участков магистральных теплопроводов методом эталона - Цаканян, О.С.; Голощапов, В.Н.; Кошель, С.В.; Ганжа, Н.Г. (Проблемы машиностроения, 2017)
Разработана методика измерений и конструкция измерительного прибора для определения уровня тепловых потерь на любом участке трубопроводов независимо от типа тепловой изоляции. Прибор представляет собой установленный на трубу корпус с экранами на внутренних поверхностях и отверстиями снизу и сверху для датчиков измерения температуры и расхода воздуха, по которым определяются тепловые потери в окружающую среду. Предварительно прибор тарируется в лабораторных условиях с применением эталона тепловой мощности, в котором она равномерно распределена по поверхности участка, имитирующего трубопровод. Эталон представляет собой модель участка трубопровода, содержащую нагреватель и интегральный датчик температуры. Изменяя диаметр отверстия в торцевых крышках прибора, его можно применять для измерения тепловых потерь трубопроводов различного диаметра. Розроблено методику вимірювань і конструкцію вимірювального приладу для визначення рівня теплових втрат на будь-якій ділянці трубопроводів незалежно від типу теплової ізоляції. Прилад являє собою встановлений на трубу корпус з екранами на внутрішніх поверхнях і отворами знизу та зверху для датчиків вимірювання температури й потоку повітря, якими визначаються теплові втрати в навколишнє середовище. Попередньо прилад градуюється в лабораторних умовах із застосуванням еталона теплової потужності, в якому вона рівномірно розподілена поверхнею ділянки, що імітує трубопровід. Еталон являє собою модель ділянки трубопроводу, що містить нагрівач та інтегральний датчик температури. Змінюючи діаметр отвору в торцевих кришках приладу, його можна застосовувати для вимірювання теплових втрат трубопроводів різного діаметра. Currently, thousands of kilometers of heat pipes operated with worn insulation. A significant part of heat energy is lost to the environment. To measure the magnitude of heat losses on the pipeline very difficult, and the accuracy of measurements using the current methods depends on seasons, temperature and humidity, coolant temperature, state of heat insulation and other factors. The developed measurement technique and design of the measuring device allows to determine the level of heat loss in any pipe section regardless of the type of thermal insulation. The measuring device is a mounted on the tube housing with screens on the inner surfaces and openings top and bottom for sensors measuring temperature and air flow, which determines the heat loss into the environment. The device is pre-calibrated in the laboratory using standard heat capacity in which it is uniformly distributed over the surface, simulating the pipeline. The benchmark is a model of the pipeline section containing the heater and integral temperature sensor. The presence of screens and good insulation of the device allows you to convert all radiant heat energy in the convection. This allows to take into account all heat losses of the pipeline. Changing the diameter of the holes in the end caps of the device, it can be used to measure the heat losses from the pipelines of various diameter.